Modern Dearomative Enlargement of Heteroaromatic Rings - Moreau, Xavier; Ghiazza, Clément (Synthesis, 2024)
Breaking aromaticity by inserting additional atoms within the skeleton of heteroaromatic rings has gained significant attention over the years. As part of the emerging concept of ‘skeletal editing’, this short review retraces the recent progress made on dearomative enlargement reactions of both five- and six-membered heterocycles.1 Introduction2 Dearomative Enlargement of Five-Membered Rings2.1 Pyrroles, Furans, Thiophenes and Their Fused Analogues2.2 Pyrazoles, Isoxazoles, Isothiazoles and Their Fused Analogues3 Dearomative Enlargement of Six-Membered Rings4 Conclusion and Perspectives
Keywords: dearomatization; ring expansion; atom insertion; heterocycles; skeletal editing; carbenes